The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0735-1097(01)01339-0
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenosis with severe left ventricular dysfunction and low transvalvular pressure gradients

Abstract: In patients with AS, LV dysfunction and low transvalvular gradients, contractile reserve on DSE is associated with a low operative risk and good long-term prognosis after valve surgery. In contrast, operative mortality remains high in the absence of contractile reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(71 citation statements)
references
References 26 publications
2
68
0
1
Order By: Relevance
“…The main limitation of the indices used in previous studies 1,3,4,5,7 to discriminate TS from PS AS is that they are all dependent on the magnitude of flow increase achieved during DSE, which is highly variable between patients. Thus, stenotic indices may be measured at flow conditions that differ dramatically from one patient to another.…”
Section: Usefulness Of Eoa Proj To Assess Stenosis Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of the indices used in previous studies 1,3,4,5,7 to discriminate TS from PS AS is that they are all dependent on the magnitude of flow increase achieved during DSE, which is highly variable between patients. Thus, stenotic indices may be measured at flow conditions that differ dramatically from one patient to another.…”
Section: Usefulness Of Eoa Proj To Assess Stenosis Severitymentioning
confidence: 99%
“…Dobutamine stress echocardiography (DSE) has been shown to be useful to separate patients with truly severe (TS) AS and concomitant LV systolic dysfunction from those with pseudo-severe (PS) AS, in which a weakened ventricle is incapable of opening an aortic valve that is only mildly or moderately stenotic. [1][2][3][4][5][6][7] The distinction between these 2 subgroups is essential because patients with TS AS will generally benefit from aortic valve replacement (AVR), whereas those with PS AS may not. Several criteria have been proposed in the literature to…”
mentioning
confidence: 99%
“…The French multicenter study 3,12 on low-flow, low-gradient AS demonstrated that the assessment of contractile reserve during DSE provides important information for patient risk stratification. From their first report, 12 it appeared that only patients with contractile reserve should undergo surgery, as these patients were likely to have a good outcome after valve replacement, whereas survival was poor in patients without contractile reserve regardless of whether or not they had surgery. In the second larger series, however, the same authors 3 reported that outcome, although poor overall, was still significantly better with surgery, even in the group without contractile reserve.…”
Section: Low-flow Low-gradient Aortic Stenosis: a Diagnostic And Thementioning
confidence: 99%
“…6 -9 Dobutamine stress echocardiography (DSE) has been shown to be useful to distinguish TS AS from PS AS, 10,11 but whether it can reliably predict the outcome with surgery remains to be proven. Monin et al demonstrated in their initial reports 3,12 that patients with contractile reserve at DSE had a good survival after surgery, whereas outcome was poor in those without contractile reserve, regardless of the type of treatment (ie, medical or surgical). However, in a more recent study, 13 the same investigators reported that a substantial proportion of patients without contractile reserve may benefit from valve replacement, although it remained unclear how to identify these patients.…”
mentioning
confidence: 99%
“…This entity is generally characterized by the combination of an aortic valve EOA compatible with severe disease (ie, 1.0 cm 2 or less, or 0.6 cm 2 /m 2 or less when indexed for body surface area), a low transvalvular gradient (eg, mean gradient less than 40 mmHg), and a low ejection fraction (40% or less). Indeed, operative mortality for AVR in these patients is high, ranging between 8% and 33% depending on the study (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Moreover, this mode of presentation also represents a diagnostic challenge because at the outset, it is impossible to distinguish between patients having truly severe AS (TS AS) from those having pseudosevere AS (PS AS).…”
Section: Low-flow Low-gradient As: a Diagnostic And Therapeutic Chalmentioning
confidence: 99%